Albania : Poverty Reduction Strategy Paper-National Strategy for Development and Integration. (IMF Staff Country Reports; Country Report, 2008)
This paper focuses on the Poverty Reduction Strategy Paper-National Strategy for Development and Integration (PRSP-NSDI) for Albania. The paper provides an overview of the key challenges facing the country. It presents a brief statement of the national vision, identifies the strategic priorities, and articulates the strategic goals to be achieved. The paper also summarizes the key points of each of the underlying strategies by strategic priority, and discusses the main changes in the distribution of resources across broad sectors that will be needed in the period 2007-13.